2018
DOI: 10.1155/2018/2527406
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Enhance Murine Monocyte Proliferation in Bone Marrow and Prime Them into an Inflammatory Phenotype through MAPK Signaling

Abstract: Objective Increased monocytes, particularly the inflammatory subset, are associated with accelerated atherosclerosis in diabetes through thus far incompletely defined mechanisms. The present study tested the hypothesis that advanced glycation end products (AGEs) promote bone marrow monocytes to proliferate and drive them into an inflammatory phenotype. Methods and Results In vivo, AGEs (25 mg/kg i.p. for 7 days) increased proportions of CD115+ monocytes and the inflammatory subset, the CD115+Ly6Chigh cells, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…Murine monocytes from mice treated with modified BSA showed an increased proportion of proinflammatory monocyte phenotype accompanied by an increased gene expression of proinflammatory cytokines such as IL-6 and TNF-α. However, no change was observed in the expression of anti-inflammatory cytokines [166]. However, the exact modifications that BSA underwent were not clear in this study.…”
contrasting
confidence: 61%
See 1 more Smart Citation
“…Murine monocytes from mice treated with modified BSA showed an increased proportion of proinflammatory monocyte phenotype accompanied by an increased gene expression of proinflammatory cytokines such as IL-6 and TNF-α. However, no change was observed in the expression of anti-inflammatory cytokines [166]. However, the exact modifications that BSA underwent were not clear in this study.…”
contrasting
confidence: 61%
“…However, the exact modifications that BSA underwent were not clear in this study. In the same study, they observed increased proliferation and expression of TNF-α, IL-6, which was MAPK dependent as proven by the incubation with MAPK inhibitors [166]. In another study, exposure of mouse peritoneal macrophages to glucose-, MGO-and glyoxylic acid-modified BSA increased the TNF-a secretion.…”
mentioning
confidence: 73%
“…During hyperglycaemia, binding of AGEs to RAGE elevates adhesion molecule expression, production of cytokines and growth factors via the activation of ERK, JNK and PI3K pathways. AGEs directly stimulate monocytes to produce inflammatory mediators such as the ILs and TNF‐α, and thereby further enhance local inflammation of the vascular wall (Jin et al, 2018). Moreover, excessive production of ROS induces vascular inflammation in ECs via up‐regulating the adhesion molecules ICAM‐1 and VCAM‐1 (Daiber et al, 2020).…”
Section: Sglt‐2is Inhibit the Inflammatory Response Of Ecs To Differe...mentioning
confidence: 99%
“…Various innate immune cells in the skin express RAGE, including mononuclear phagocytes, DCs, and keratinocytes [31,32]. AGE binding to mononuclear phagocytes stimulates their chemotaxis towards skin and the production of IL-1β and TNF-α [33,34]. In DCs, exposure to AGEs induces greater production of IL-6 and activation of the nuclear factor kappa B (NF-κB) pathway [35].…”
Section: Calcinosis Cutis With Normal Serum Calcium and Phosphatementioning
confidence: 99%